A WAY TO PREVENT THE PANDEMIC OUTBREAK OF nCOVID-19 IN INDIA - PAL, NIKITA; GOSWAMI, SHAMBADITYA; SINGH, RAVINDRA PAL; SINGH, PRASHANT (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Not applicable because it is letter to editor